Prevalence and risk factors of feline calicivirus and assessment of knowledge, attitudes and practices among cat owners in Pakistan (VETERINARIA, 2025)
Feline calicivirus is an upper respiratory tract infection characterized by mouth ulcers and runny eyes, and one of the commonest viral infections in cats. This study was conducted to determine the prevalence of feline calicivirus and to identify the public’s knowledge, risk factors, attitude and practices towards calicivirus and general care of cats in Pakistan. The prevalence was determined based on diagnostic data (pathological observations and serological tests) from veterinary clinics in the study area during 2021. A questionnaire was designed to access the sociodemographic, knowledge, attitude and practices regarding feline calicivirus among 298 pet owners. The overall prevalence of feline calicivirus was 17.1%. The majority (62.75%) of the pet owners showed overall poor knowledge about the transmission of the virus and its infectiousness. A poor attitude towards the prevention of feline calicivirus was also observed in 52.68% of respondents. Most pet owners (62.75%) had poor values regarding the cleanliness of their cats. Because most surveys were completed by responders living in urban areas, very few cats were exposed to toxins such as pesticides. Despite not knowing much about the virus itself, responders were keen to keep their feline pets healthy with good hygiene; however, only a minimum ensured it.
Keywords: Islamabad; knowledge; mouth ulcers; prevalence; risk factors